Homology: A Human Rights Poem - Verhoye, Anna (In Factis Pax: Journal of Peace Education and Social Justice, 2014)
Conceived from a homosocial bond, born into oppression, I traversed the symbolic boundary leaving behind an identity that was not even my own.